2018
DOI: 10.3389/fimmu.2018.00666
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Lymphoproliferative Disease Type 1: A Clinical and Molecular Perspective

Abstract: X-linked lymphoproliferative disease (XLP) was first described in the 1970s as a fatal lymphoproliferative syndrome associated with infection with Epstein–Barr virus (EBV). Features include hemophagocytic lymphohistiocytosis (HLH), lymphomas, and dysgammaglobulinemias. Molecular cloning of the causative gene, SH2D1A, has provided insight into the nature of disease, as well as helped characterize multiple features of normal immune cell function. Although XLP type 1 (XLP1) provides an example of a primary immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 104 publications
1
54
0
3
Order By: Relevance
“…Such immunodeficiencies are often characterized by hemophagocytic lymphohistiocytosis (HLH), resulting from secondary immune activation in response to IFNγ and other cytokines . CTL and NK function are essential for responses to chronic infections such as those with EBV, a common human gamma‐herpesvirus that persists latently in B cells . In immunocompromised patients, EBV reactivation can cause lymphoproliferative disorders and lymphoid malignancies; many PIDs are associated with EBV‐mediated pathology .…”
Section: Cd8+ T‐cell Function In Apdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such immunodeficiencies are often characterized by hemophagocytic lymphohistiocytosis (HLH), resulting from secondary immune activation in response to IFNγ and other cytokines . CTL and NK function are essential for responses to chronic infections such as those with EBV, a common human gamma‐herpesvirus that persists latently in B cells . In immunocompromised patients, EBV reactivation can cause lymphoproliferative disorders and lymphoid malignancies; many PIDs are associated with EBV‐mediated pathology .…”
Section: Cd8+ T‐cell Function In Apdsmentioning
confidence: 99%
“…XLP1 is characterized by an inability of CTLs and NK cells to kill EBV‐infected B cells . Combined with a defect in T‐cell restimulation‐induced cell death (RICD), patients with XLP1 develop fatal lymphoproliferation and HLH, most often secondary to EBV infection.…”
Section: Cd8+ T‐cell Function In Apdsmentioning
confidence: 99%
“…This gene encodes the SLAM-associated protein (SAP) which is a key regulator of immune function in T, NK, and NKT cells and defects in this protein may lead to the cellular and humoral immune defects characterized in patients [2]. Clinical manifestations vary and include hemophagocytic lymphohistiocytosis (HLH), lymphoma, and dysgammaglobulinemia [2,3] but patients can experience a wide range of phenotypes associated with immune dysregulation, even independent of Epstein-Barr virus (EBV) infection [3,4]. Although historically associated with EBV infection, a recent study showed 35% of patients with XLP1 had no evidence of previous EBV infection and patients are often diagnosed based on positive family history alone [4].…”
mentioning
confidence: 99%
“…To investigate the role of SAP in the Jurkat-SLAMF6 ∆17-65 cells, we knocked down the residual SAP with siRNA and observed that IL-2 secretion increased further (Figure 6c,d). XLP (X-linked lymphoproliferative disease) is a fatal immune dysregulation syndrome, caused by a mutation creating non functioning SAP and characterized by unremitting Epstein-Barr virus (EBV) infections, dysgammaglobulinemia, and lymphoma 28 . PBMCs obtained from two XLP patients with SAP mutations displayed a very high IFN-γ secretion of 9000 pg/ml, compared to 250 pg/ml secreted by PBMCs from healthy donors tested in the same experiment and under the same activation conditions (Figure 6e).…”
Section: Slam-associated Protein (Sap) Is Reduced In Activated Slamf6mentioning
confidence: 99%